Statistics on mortality following acute myocardial infarction in 842 897 Europeans. Issue 1 (26th July 2019) - Alabas, Oras A; Jernberg, Tomas; Pujades-Rodriguez, Mar; Rutherford, Mark J; West, Robert M; Hall, Marlous; Timmis, Adam; Lindahl, Bertil; Fox, Keith A A; Hemingway, Harry; Gale, Chris P
Abstract: Aims: To compare ST-segment elevation myocardial infarction (STEMI) and non-STEMI (NSTEMI) mortality between Sweden and the UK, adjusting for background population rates of expected death, case mix, and treatments. Methods and results: National data were collected from hospitals in Sweden [ n = 73 hospitals, 180 368 patients, Swedish Web-system for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies (SWEDEHEART)] and the UK [ n = 247, 662 529 patients, Myocardial Ischaemia National Audit Project (MINAP)] between 2003 and 2013. There were lower rates of revascularization [STEMI (43.8% vs. 74.9%); NSTEMI (27.5% vs. 43.6%)] and pharmacotherapies at time of hospital discharge including [aspirin (82.9% vs. 90.2%) and (79.9% vs. 88.0%), β-blockers (73.4% vs. 86.4%) and (65.3% vs. 85.1%)] in the UK compared with Sweden, respectively. Standardized net probability of death (NPD) between admission and 1 month was higher in the UK for STEMI [8.0 (95% confidence interval 7.4–8.5) vs. 6.7 (6.5–6.9)] and NSTEMI [6.8 (6.4–7.2) vs. 4.9 (4.7–5.0)]. Between 6 months and 1 year and more than 1 year, NPD remained higher in the UK for NSTEMI [2.9 (2.5–3.3) vs. 2.3 (2.2–2.5)] and [21.4 (20.0–22.8) vs. 18.3 (17.6–19.0)], but was similar for STEMI [0.7 (0.4–1.0) vs. 0.9 (0.7–1.0)] and [8.4 (6.7–10.1) vs. 8.3 (7.5–9.1)]. Conclusion: Short-term mortality following STEMI and NSTEMI was higher in the UK compared with Sweden. Mid- and longer-term mortality remained higher in the UK for NSTEMI but was similar for STEMI. Differences in mortality may be due to differential use of guideline-indicated treatments.